2018
DOI: 10.22146/ijc.26714
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Water Repellent Layer on Glass Using Hydrophobic Compound Modified Rice Hull Ash Silica

Abstract: In this study water repellent layered glass has been prepared by coating silica (SiO2) combined with a hydrophobic silane compound. SiO2 was extracted from rice hull ash and two silane compounds, namely hexadecyltrimethoxysilane (HDTMS) and trimethylchlorosilane (TMCS) were used. Coating was performed through two deposition techniques, i.e. one step (mono-layer) and layer by layer (LBL, multi-layer). The effect of silane to SiO2 mole ratio, silane type and layer number on the glass characters was evaluated. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…It was observed that, in most cases, it is a combination of these objectives [1]. Many techniques have been carried out to prepare hybrid coatings including plasma etching [2], layer-by-layer film formation [3], electrospinning [4], chemical vapor deposition (CVD) [5] and the sol-gel process [6]. Compared with the mentioned methods, the sol-gel process is the most used method to produce the hybrid silica coatings because: (a) it allows the control of the product's chemical composition; (b) it is attractive for coating polymers that have melting points between 150 and 300 • C; (c) uniform coatings can easily be fabricated by dipping or spin coating; (d) is low cost and a cost-effectiveness technique and (e) ceramic, glass, metal and polymer substrates can be easily coated [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that, in most cases, it is a combination of these objectives [1]. Many techniques have been carried out to prepare hybrid coatings including plasma etching [2], layer-by-layer film formation [3], electrospinning [4], chemical vapor deposition (CVD) [5] and the sol-gel process [6]. Compared with the mentioned methods, the sol-gel process is the most used method to produce the hybrid silica coatings because: (a) it allows the control of the product's chemical composition; (b) it is attractive for coating polymers that have melting points between 150 and 300 • C; (c) uniform coatings can easily be fabricated by dipping or spin coating; (d) is low cost and a cost-effectiveness technique and (e) ceramic, glass, metal and polymer substrates can be easily coated [7].…”
Section: Introductionmentioning
confidence: 99%
“…The dried sample was then added with 4 M NaOH solution, then stirred with a magnetic stirrer at 150 rpm for 3 hours on a hotplate at 70°C. Finally, the filtrate and the residue are separated so that the yield is a sodium silicate solution [23].…”
Section: Synthesis Of Sodium Silicate From Coal Fly Ashmentioning
confidence: 99%
“…Originally, TMCS has a low flash point, and it is reactive with water. To decrease the flashpoint, TMCS should be dissolved in an organic solution [23] [24]. Then, TMCS solution or silane sol is added to natrium silicate solution or silica sol.…”
Section: Preparation Of Coating On the Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…This RHA can cause an environmental problem (air pollution) and space limitations. In order to prevent the environmental problem emanating from RHA, many efforts have been made to utilize RHA in the production of silica gel [6], fire bricks [1], the hydrophobic coating on glass [7], activated carbon, soil conditioner, and biofertilizer [8].…”
Section: ■ Introductionmentioning
confidence: 99%